Innovation And Barriers To Educational Technology In Islamic Institutions: A Managerial And Implementative Review - Putri Nur Fadiyah; Arih Lailatul Fadilah; Zulfa Roikhatul Jannah; Nur Anim Jauhariyah (ICO EDUSHA, 2025)
This study aims to analyze the forms of educational technology innovation and the obstacles faced by Islamic educational institutions in their implementation, from a managerial and implementation perspective. Digital transformation in madrasas and Islamic boarding schools (pesantren) is a crucial need in this era of technological acceleration, particularly to improve the quality of learning and the effectiveness of institutional management. However, the process of implementing technology does not always run smoothly because Islamic educational institutions have unique characteristics related to values, organizational structure, and resource readiness. This study used a descriptive qualitative approach to explore in-depth the understanding, experiences, and perceptions of teachers, education staff, and madrasah administrators regarding the implemented technological innovations, as well as the various obstacles that emerged during the implementation process. The data analysis techniques used refer to the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. Data were obtained through observation, in-depth interviews, and documentation related to the e-madrasah system, LMS, computer-based exams, and various digital practices used in learning and school management. The results indicate that educational technology innovation in Islamic institutions operates in two main domains. From a managerial perspective, the implementation of digital administration systems, digital literacy training for teachers, and the development of technology-based curricula play a significant role in improving the effectiveness of institutional governance. Meanwhile, from an implementation perspective, the use of blended learning, interactive media, AI-based applications, and digital learning platforms can improve the flexibility and quality of Islamic education. However, the technology adoption process still faces significant obstacles, such as limited internet infrastructure and devices, low teacher digital competency, resistance to change, budget constraints, and a lack of digital content aligned with Islamic values. These obstacles slow the innovation diffusion process, as described in Everett M. Rogers' model, particularly at the persuasion and implementation stages. Managerial strategies such as ongoing training, collaboration to strengthen infrastructure, development of an Islamic digital curriculum, and measurable technology use policies have been shown to help mitigate obstacles and strengthen the sustainability of technological innovation in Islamic educational institutions.   Keywords: Educational Technology, Madrasah, Innovation, Islamic Education Management, Innovation Diffusion